Design and development of GIS spatial data for transmission and visualization through the web using tile tree method - Shaari, Nadzari; Daman, Daut; Kari, Sarudin; Ahmad, Ab. Rahman; Sulaiman, Sarina; Ali, Ahmad Fariz; Busu, Ibrahim (Faculty of Computer Science and Information System, 2005)
Internet technology existance has change the way of information retrieval for GIS which traditionally being developed as stand alone. Its functioning as a medium of information sharing by all levels of profesional or non profesional. However, in the effort to integrate two technologies know as Web-GIS, tehre are few issues that need to be considered. Among the issues are data storage, data transmission, presentation, analysing and manipulation of datain the web. This research done purposely to solve the issues related do data transmission. The issues that have been discussed are the high volumed of data size and limite bandwith. All of these issues gave an impact to the process of information retrieval where it received a delayed response. In order to overcome these problem, the quadtree or data divsion technique at client-side strategy have been introduced. In this technique, data for each and every layer will be divided into four quadrants in same size. Division rate is determined by the data sized for each tile. Where the process of division s repeated for each tile until the size of each tile become equal or smaller than deternine value of constraint, k. Data that been divided kept in a data structure knowns as quadTileTree. To represent data in the web, only tile that has been requested by the user will be sent out to display. From the research conducted, the layer division technique and tile structuring are able to shorten the time of spatial data transmission in web.